From Academia to Algorithms: Digital Cultural Capital of Public Intellectuals in the Age of Platformization - Lucas L. H. Wong (Social Sciences, 2025)
Scholars traditionally hold influential positions due to their cultural capital, derived from academic degrees, scholarly publications, and professional credentials. However, the rise of digital platforms has disrupted this hierarchy, placing scholars into new roles as online public intellectuals who engage in political advocacy and mobilize knowledge through public discourse. This transformation calls attention to how public intellectuals’ visibility and influence have become entangled with platform logics, leading to a reconsideration of “digital cultural capital”. Drawing theoretical insights from critical platform studies, celebrity studies, and marketing research, this article conceptually addresses three questions: (1) how traditional cultural capital transforms digitally; (2) how public intellectuals accumulate digital cultural capital; and (3) what are the risks of knowledge mobilization on platforms? This article proposes that traditional academic credentials are no longer sufficient to maintain public intellectuals’ influence, whereas visibility metrics—such as views, likes, shares, and follower counts—emerge as a digital form of “cultural capital from below”. Public intellectuals, thus, must engage in “code-switching” to navigate platform-mediated knowledge mobilization. Nevertheless, the populist tendencies embedded in cultural capital from below and the platform algorithms that enable it risk marginalizing less visible knowledge forms. Eventually, this article calls for future empirical research on how digital cultural capital and code-switching operate across geopolitical contexts, particularly within marginalized communities shaped by distinct platform logics and populist dynamics.